Kajian teori kultivasi: Implikasi konten Boys’ Love terhadap kehidupan pribadi dan sosial Kaum Fujoshi dan Fudanshi di Indonesia : Cultivation theory study: Implications of Boys’ Love content on the personal and social lives of Fujoshi and Fudanshi in Indonesia - Hanisah, Nur; Arsi, Antari Ayuning (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
This study examines the implications of boys' love (BL) content on fujoshi and fudanshi in Indonesia who live amidst social and cultural values that oppose all LGBT activities. Specifically, this study aims to discover two things: the implications of BL content on the personal and social lives of fujoshi and fudanshi. This study uses a qualitative approach to produce data in descriptive form. Data were obtained using semi-structured interviews, participant observation, and document studies. The subjects in the study were fujoshi and fudanshi in various regions in Indonesia. The purposive sampling technique was used to obtain informant data. Inclusion criteria included heterosexual fujoshi and fudanshi as well as initially heterosexual fujoshi and fudanshi. After that, the data were transcribed verbatim and processed using data source triangulation techniques. The results of the study show several things. First, in personal life, BL content can foster homosexual tolerance for fujoshi and fudanshi. However, there is still an inner conflict with the social values and beliefs of fujoshi and fudanshi related to the view that LGBT activities are deviant. In addition, BL content can also make fujoshi and fudanshi better understand their sexual orientation. It can foster fujoshi and fudanshi sexual imagination which is contrary to the biological conditions of fujoshi and fudanshi in real life. Second, based on cultivation theory, BL content can cause changes in fujoshi and fudanshi social relations to a wider realm through the community. However, this can eventually lead to conflict between communities due to having different tensions.